2021
DOI: 10.1007/s11030-021-10251-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential phytochemical inhibitors of SARS-CoV-2 helicase Nsp13: a molecular docking and dynamic simulation study

Abstract: Graphic abstract The SARS-CoV-2 helicase Nsp13 is a promising target for developing anti-COVID drugs. In the present study, we have identified potential natural product inhibitors of SARS-CoV-2 Nsp13 targeting the ATP-binding site using molecular docking and molecular dynamics (MD) simulations. MD simulation of the prepared crystal structure of SARS-CoV-2 Nsp13 was performed to generate an ensemble of structures of helicase Nsp13 capturing the conformational diversity of the ATP-binding site. A natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Amongst other helicase drug screening studies, a docking study screened nucleoside analogs for helicase activity and identified pritelivir as a potential drug candidate [ 65 ]. Another molecular docking and MD simulation study identified potential natural product inhibitors of helicase targeting the ATP-binding site which included picrasidine-N and -M, epiexcelsin, isorhoeadine, and euphorbetin [ 66 ]. Another study used fragment screening to identify possible druggable pockets on the Nsp13 helicase, identifying a favorable allosteric site on the N-terminal zinc binding domain that is a Nsp8:Nsp13 protein–protein interaction site [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Amongst other helicase drug screening studies, a docking study screened nucleoside analogs for helicase activity and identified pritelivir as a potential drug candidate [ 65 ]. Another molecular docking and MD simulation study identified potential natural product inhibitors of helicase targeting the ATP-binding site which included picrasidine-N and -M, epiexcelsin, isorhoeadine, and euphorbetin [ 66 ]. Another study used fragment screening to identify possible druggable pockets on the Nsp13 helicase, identifying a favorable allosteric site on the N-terminal zinc binding domain that is a Nsp8:Nsp13 protein–protein interaction site [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The key amino acid residues of the ATP-binding site are six in number and are Lys288, Ser289, Asp374, Glu375, Gln404, and Arg567 [ 52 ]. Dihydroxyacidissiminol showed the predicted binding energy of −7.6 kcal/mol with Nsp13 helicase.…”
Section: Resultsmentioning
confidence: 99%
“…Outbreaks of nosocomial infection caused by A . baumannii resistant to imipenem have reached the proportions of a global health emergency [ 52 ]. According to the International Network for the Study and Emergency Prevention of Antimicrobial Resistance [ 61 ], multi-resistant A .…”
Section: Discussionmentioning
confidence: 99%
“… 539 Meanwhile, SARS-CoV-2 helicase (nsp13) was another attractive target. 540 Vivek-Ananth et al 541 estimated the docking scores of 10510 drug-like phytochemicals from PubChem to helicase, and the top five compounds were further evaluated by MM/PBSA calculations. In another work, 131 compounds were docked to helicase.…”
Section: Methods and Approachesmentioning
confidence: 99%